REPRESENTASI PATRIARKI KELUARGA BATAK (STUDI SOSIOLOGI FILM: TOBA DREAMS) - Kiki, Evrison Frans; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to find out how far a film that is one of the art products, can serve as a container to represent social reality that exist in society. This study used a qualitative approach to discuss Toba Dreams film as a film that represents patriarchal culture which identical with male superiority and masculinity. In this research, the main thing that becomes the most important thing is the relationship between the actors in the film that describe through the dialogue, scenes and storyline. The above will create a social structure that reflects the reality which exists in society. In addition, cultural aspects are also part of this research because this aspect is considered to be influential in the film. This aspect is a form of the values or ideology made by the director into the film. The cultivation of this value has the motivation to describe the ideal situation in society or can also be used as a director's view of a particular social context of society. The results of this study indicate that the Toba Dreams film is not only a part of the art but can be used as a scientific by using the sociological view by describing of life people in Indonesia. The scene in the film reflects the patriarchal attitude that has become a culture in some societies.Keywords: Film, Patriarchy, Toba Dreams